2020
DOI: 10.1093/nar/gkaa304
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome profiling in archaea reveals leaderless translation, novel translational initiation sites, and ribosome pausing at single codon resolution

Abstract: High-throughput methods, such as ribosome profiling, have revealed the complexity of translation regulation in Bacteria and Eukarya with large-scale effects on cellular functions. In contrast, the translational landscape in Archaea remains mostly unexplored. Here, we developed ribosome profiling in a model archaeon, Haloferax volcanii, elucidating, for the first time, the translational landscape of a representative of the third domain of life. We determined the ribosome footprint of H. volcanii to be comparabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 76 publications
6
42
0
Order By: Relevance
“…The occurrence of OLGs is accepted in viral genomes (Pavesi et al, 2018) and since there is a constant gene flow between bacteria and their viruses (Kirchberger et al, 2020), shaping bacterial genome evolution (Koskella and Brockhurst, 2014), we propose that long overlaps of ORFs or embedded gene-ORFs, hence, overlapping genes, should also be expected in bacteria (also see Meydan et al, 2018). This hypothesis is supported by several observations: As mentioned, differential transcription of overlapping genome regions (Figure 1A) and translation of so-called non-coding RNAs (Neuhaus et al, 2017) has been reported, also in archaea (Gelsinger et al, 2020). Further, at least a few OLGs in other bacterial species have been described (e.g., Balabanov et al, 2012; Kim et al, 2009).…”
Section: Introductionsupporting
confidence: 69%
“…The occurrence of OLGs is accepted in viral genomes (Pavesi et al, 2018) and since there is a constant gene flow between bacteria and their viruses (Kirchberger et al, 2020), shaping bacterial genome evolution (Koskella and Brockhurst, 2014), we propose that long overlaps of ORFs or embedded gene-ORFs, hence, overlapping genes, should also be expected in bacteria (also see Meydan et al, 2018). This hypothesis is supported by several observations: As mentioned, differential transcription of overlapping genome regions (Figure 1A) and translation of so-called non-coding RNAs (Neuhaus et al, 2017) has been reported, also in archaea (Gelsinger et al, 2020). Further, at least a few OLGs in other bacterial species have been described (e.g., Balabanov et al, 2012; Kim et al, 2009).…”
Section: Introductionsupporting
confidence: 69%
“…Hence, in Thermococcus onnurineus (Cho et al, 2017), Thermococcus kodakarensis (Jäger et al, 2014), Methanolobus psychrophilus (Li et al, 2015), Methanosarcina mazei (Jäger et al, 2009), P. abyssi (Toffano-Nioche et al, 2013), and Pyrococcus furiosus (Grünberger et al, 2019), the abundance of leaderless mRNA is around 15% only. This is in contrast with the high percentage of leaderless mRNA observed in Saccharolobus solfataricus (69%; Wurtzel et al, 2010) and Pyrobaculum aerophilum (Slupska et al, 2001;Ma et al, 2002), both being crenarchaeaota, and the euryarchaeota Haloferax volcanii (72%; Babski et al, 2016;Gelsinger et al, 2020). Interestingly, a quick analysis of the annotated translation initiation regions in the available Lokiarchaeaote genome (Imachi et al, 2020) suggests that SD sequences are not prevalent ( Figure 4A).…”
Section: Archaeal Mrnasmentioning
confidence: 83%
“…The differences in 5′UTR of mRNAs reflect some diversity in translation initiation mechanisms (Tolstrup et al, 2000;Slupska et al, 2001;Torarinsson et al, 2005;Brenneis et al, 2007;La Teana et al, 2013;Kramer et al, 2014;Schmitt et al, 2019). Recent genome-wide studies, most of them based on differential RNA-seq methods, highlighted mRNA organization in various archaeal branches (Jäger et al, 2009(Jäger et al, , 2014Wurtzel et al, 2010;Toffano-Nioche et al, 2013;Li et al, 2015;Babski et al, 2016;Cho et al, 2017;Smollett et al, 2017;Grünberger et al, 2019;Gelsinger et al, 2020). Identification of transcription start points is particularly important in Archaea, where most gene annotations are generated from general computational pipelines that are not fully reliable.…”
Section: Archaeal Mrnasmentioning
confidence: 99%
“…RNA was assessed for DNA contamination using PCR, and RNA quality was determined using a 2100 Bioanalyzer (Agilent genomics). cDNA libraries for sequencing were constructed using a ScriptSeq Complete v2 RNA-Seq Library Preparation kit (Illumina), including depletion of rRNA using the Ribo-Zero rRNA removal beads for bacteria (a common practise for archaeal RNA sequencing 27 , 28 ) and barcoded with the ScriptSeq Index PCR Primers (Set 1). cDNA was sequenced using a 150-cycle MiSeq reagent kit v3.…”
Section: Methodsmentioning
confidence: 99%